2016
DOI: 10.1136/medethics-2016-103621
|View full text |Cite
|
Sign up to set email alerts
|

Means, ends and the ethics of fear-based public health campaigns

Abstract: Controversy has swirled over the past three decades about the ethics of fear-based public health campaigns. The HIV/AIDS epidemic provided a context in which advocacy groups were almost uniformly hostile to any use of fear, arguing that it was inherently stigmatising and always backfired. Although this argument was often accepted within public health circles, surprisingly, the bioethicists who first grappled with this issue in terms of autonomy and coercion in the 1980s were not single-minded: fear could be au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…Messages about the negative health consequences of lifestyle behaviours have been shown to provide motivation for positive change in other public health campaigns. 10,34,35 Given the observed increase in knowledge reflects the campaign message about the health effects of drinking too many SSBs, this provides support for the campaign as a driver of the increase. These findings also support the benefits of a specific, actionable health-message in public health communication.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Messages about the negative health consequences of lifestyle behaviours have been shown to provide motivation for positive change in other public health campaigns. 10,34,35 Given the observed increase in knowledge reflects the campaign message about the health effects of drinking too many SSBs, this provides support for the campaign as a driver of the increase. These findings also support the benefits of a specific, actionable health-message in public health communication.…”
Section: Discussionmentioning
confidence: 70%
“…As a mechanism to provide motivation for lifestyle change, the campaign aimed to increase awareness and understanding of the health consequences of SSB consumption. Messages about the negative health consequences of lifestyle behaviours have been shown to provide motivation for positive change in other public health campaigns . Given the observed increase in knowledge reflects the campaign message about the health effects of drinking too many SSBs, this provides support for the campaign as a driver of the increase.…”
Section: Discussionmentioning
confidence: 86%
“…Stigma could be attributed to: extremely poor health (Lecomte et al, 2013); social issues, such as violence (McKetin et al, 2014); and media campaigns sensationalising the deleterious health, social and justice outcomes associated with methamphetamine use in a way likely to stigmatise, rather than assist methamphetamine users (Australian Government, 2016; Meth Project Foundation, 2016; Multnomah County Sherrif's Office, 2016)(Australian Federation of Aids Organisations, 2015; Kiejda, 2015). Prior literature suggests that campaigns that utilise shock or fear with the aim of changing behaviours, must also emphasise the treatment options available in order to be effective (Bayer and Fairchild, 2016;Soames Job, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Durkin, Biener, and Wakefield (2009) found that fear-based appeals increased smoking cessation rates. Similarly, Bayer and Fairchild (2016) argue that although fear-based public health campaigns may be controversial, a growing body of evidence suggests that they are successful in changing norms. In contrast, our findings suggest that negative associations and the use of fear may limit the effectiveness of FGM/C abandonment initiatives.…”
Section: Discussionmentioning
confidence: 99%